nfluence of religion in politics and its position withregard to the configuration of political opposition inColombia (2013)
This paper presents a meticulous but brief report about how political history of Latin America and particularly the Colombian, has always been marked by events in which religion or, specifically, the representatives of these organizations have been involved in social affairs that subsequently translates into political demonstrations. Which, often, influence in the administration of the State, since they do not only hold a moral-political power, but usually are covered by the capital. This causes that those confessions that do not receive the described qualities, are seriously disadvantaged by such organizations using many times the power of the State, by action or omission to fulfill its objective; that is, to bequeath them legally, forcing them to abandon their beliefs, traditions and customs; in other words, stripping them of any trait related to their idiosyncrasies and therefore preventing the Colombian people to get political culture and a critical judgment against social reality